The use of HPLC method for analysis of prazosin hydrochloride suitable for a chemical-toxicological investigation - Mamina, Оlena; Kabachny, Volodimir (ScienceRise: Pharmaceutical Science, 2017)
Aim of research is the identification and quantification of prazosin hydrochloride according to the unified HPLC method that based on application: reverse-phase chromatography, linear gradient and multichannel UV-detecting substances. The method allows obtaining reliable results of studies of drugs and mixtures in biological objects. Materials and methods. HPLC chromatography was performed on microcolumn liquid chromatograph "Milichrome A-02" ("EcoNova" Novosibirsk, Russia) in reverse-phase variant. In this work the reagents of the qualification "for HPLC" and "PFA" were used. Prazosin hydrochloride was isolated from tablets Prazosin-Ratiofarm (50 pcs.) of 1 mg (Merkel GmbH & Co., Germany). Purity of the substance was checked by TLC and UV spectroscopy and the quality complies with the requirements of the SPhU. Results of the research. During identification, absolute retention time (15.99–16.12 min) and retention volume (1598.5–1611.5 μl) of prazosin hydrochloride spectral relations, detection limit of medicine in the sample (8.0 µg / ml or 32.0 ng of sample), values of coefficients peak symmetry (0.96–1.04) and coefficients of capacity ratio (9.44–9.96) were determined. The regression coefficients of calibration curve were calculated by the method of least squares with the equation of the line S = 0.00134 С. Correlation coefficient equaled 0.9993. Validation characteristics of HPLC-method for determination of prazosin hydrochloride: linearity range (10.0–200.0 µg / ml), limit of quantitative determination (10.0 µg / ml or 40 ng of sample), correctness and accuracy, which based on the quantitative determination results of the preparation by HPLC method in the model solutions (RSD=67.9 %) were calculated. It is established that the relative uncertainty of the average result was not exceeded +1.89 % when using the proposed method of HPLC analysis of prazosin hydrochloride in model solutions. Conclusion. Identification and quantification of prazosin hydrochloride was carried out using a unified HPLC method suitable for a chemical toxicological study